2010
DOI: 10.1097/qad.0b013e32833ac9e6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of HIV-1 transmission in men who have sex with men: a combined clinical, epidemiological and phylogenetic approach

Abstract: Onward transmission of HIV among MSM is significantly associated with recent infection, sexually transmitted diseases and higher viral load, and reduced by effective HAART. The majority of new infections appear to occur from individuals whose infection was undiagnosed at the time of transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 37 publications
5
106
0
Order By: Relevance
“…A UK study using phylogenetic analysis and clinical data found that HIV transmission was strongly associated with younger age, recently acquired HIV infection, being ART naive or having concomitant STI. The majority of new infections appeared to be acquired from men who had not yet been diagnosed with HIV (405). Mathematical modelling suggests that the proportion of new infections attributable to transmission from undiagnosed men is 82% (184).…”
Section: Antiretroviral Post-exposure Prophylaxis For Sexual Exposurementioning
confidence: 99%
“…A UK study using phylogenetic analysis and clinical data found that HIV transmission was strongly associated with younger age, recently acquired HIV infection, being ART naive or having concomitant STI. The majority of new infections appeared to be acquired from men who had not yet been diagnosed with HIV (405). Mathematical modelling suggests that the proportion of new infections attributable to transmission from undiagnosed men is 82% (184).…”
Section: Antiretroviral Post-exposure Prophylaxis For Sexual Exposurementioning
confidence: 99%
“…[8][9][10] Sexual networks may extend outside campuses and involve groups of MSM with higher infection prevalence. 11 Recent data on epidemiology and transmission of HIV among college students in the United States are lacking.…”
mentioning
confidence: 99%
“…False negative diagnoses could also lead to further HIV transmission by providing a false sense of security. As many as 70% of new HIV transmissions may be attributable to undiagnosed HIV infection [35], with early/acute infection contributing to 10–50% of new HIV transmissions [36]. Furthermore, misdiagnoses may also undermine public trust in test results as well as trust in health services.…”
Section: What Are the Consequences And Costs Of Misdiagnosis?mentioning
confidence: 99%